Smart Garbage Monitoring - Asnazulfadhli Zariman; Muhammad Syazwan Abd Latif; Ammar Asyraf Ismail (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2019)
This study develops a garbage monitoring based on Internet of Things (IoT) that can be used in the garbage management system in the city. Through this project, it can help to keep the city clean from the rubbish. By using Blynk as an application, this project will monitor the garbage bins and send the notification to the garbage collector about the level of garbage collected in the garbage bins. By receiving the information about the garbage level, the garbage collector will come on time in collecting the rubbish. The objective and purpose in developing smart garbage monitoring system is to save the time between users and the garbage collector.